Mathematical communication ability students based on learning motivation in the COVID-19 pandemic - Muhammad, Malim; Purwanto, Joko; Christiyansyah, Octarina (Journal of physics. Conference series, 2021)
The research aims to describe Tenth-grade students’ mathematics communication competence of vocational high school of Bina Teknologi, in Purwokerto Indonesia. The research used a qualitative method with Miles and Huberman model consisting of data reduction, data display, and taking a conclusion. The research subjects were Tenth-grade of Network and Computer Engineering class students obtained through purposive sampling. The students were grouped into three categories based on their learning motivation, namely students with high learning motivation, students with medium learning motivation, and students with low learning motivation. Two respondents, from each category, were chosen to be interviewed. The methods of data collection were questionnaires, tests, interviews, and documentation. The used validation test was technique triangulation. The research result shows that Subjects with high learning motivation were able to use language and mathematical symbols in daily events, were able to interpret mathematical ideas based on the graphs presented, were able to provide easy-to-understand arguments, and were able to draw graphs based on mathematical situations or problems. Subjects with learning motivation are able to use language and mathematical symbols in everyday events, are able to provide easy-to-understand arguments, and are able to draw graphs based on situations or math problems. Subjects with low learning motivation are able to use language and mathematical symbols in everyday events and are able to provide easy-to-understand arguments.